Phytoseiid mites (Acari: Phytoseiidae) from Egypt, with new records, descriptions of new species, and a key to species - Abo-Shnaf, Reham I. A.; Moraes, Gilberto J. De (Zootaxa, 2014)
The present paper refers to the identification of phytoseiid specimens newly collected by the first author of this paper and her collaborators, as well as to the examination of type specimens of species previously described from Egypt. The taxonomy of phytoseiid mites has been studied in Egypt since 1967. Until now, 78 nominal species have been recorded, of which 60 are valid. One of those species, Phytoseius plumifer (Canestrini & Fanzago), appears to be based on an incorrect record. An additional species (Typhlodromus hellei Hassan, Afifi & Nawar), described from Egypt, is not sufficiently characterised to allow its correct generic classification and the determination of its validity. Eight new records are reported in this paper, including two new species, Proprioseiopsis ismailiaensis n. sp. and Typhlodromus (Anthoseius) fayoumensis n. sp., which are described. Complementary descriptions of 11 known species are given. An updated survey of all species reported from Egypt and a taxonomic key to separate them are also presented. Six new synonymies are proposed.